2013
DOI: 10.1186/2251-7715-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Domestic scale vermicomposting for solid waste management

Abstract: Purpose The long-term use of manure as a source of nutrients can promote phosphorus (P) leaching, especially in sandy soils. The aim was to evaluate P mobility from organic and mineral sources in columns, linked with the Dystric Xeropsamments adsorption characteristics with long-term organic fertilization regime. Methods The mineral, chemical, and physical properties of the samples were characterized, including Langmuir adsorption and desorption kinetics. The P mobility was determined in one leaching experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Pathma and Sakhivel [8], reported that vermicompost is process of non-thermophilic, bio-oxidative process with help of earthworm and microbes. Compost carbon:nitrogen ratio of the compost was higher than raw waste [25].…”
Section: Vermicomposting Characteristics and Processmentioning
confidence: 78%
“…Pathma and Sakhivel [8], reported that vermicompost is process of non-thermophilic, bio-oxidative process with help of earthworm and microbes. Compost carbon:nitrogen ratio of the compost was higher than raw waste [25].…”
Section: Vermicomposting Characteristics and Processmentioning
confidence: 78%
“…We used a questionnaire that designed by Hassanvand et al [1] that is consist of five sections: (1) Quantity of HWs generation, (2) Separation, packaging, and labeling of HWs, (3) temporary storage method of HWs, (4) Discharge or collection frequency of HWs, and (5) treatment and final disposal method of HWs [[2], [3], [4], [5], [6], [7], [8]].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Past experience teaches us to replace the use of chemical fertilizer with the organic manure using earthworms. One of the most important earthworm families is Lumricidae, and one of its members, Eiseniafetida, can be used to stabilize organic waste the process called "Vermicomposting" or composting with worms 5 . Applications of vermicompost increases in soil health, soil minerals, water holding capacity, soil microorganism and nutritional values of yielding crop as well as decreases plant pests population 6 .…”
Section: Quick Response Codementioning
confidence: 99%